2005
DOI: 10.1177/003693300505000210
|View full text |Cite
|
Sign up to set email alerts
|

Walking at Work: A Pedometer Study Assessing the Activity Levels of Doctors

Abstract: Walking at work does provide a substantial proportion of a doctor's recommended daily activity quota. However, it is still necessary to engage in additional, out-of-hours exercise in order to consistently meet the current recommendations for physical exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 3 publications
0
17
0
2
Order By: Relevance
“…25 Our study showed that activity of CV specialists is higher than the general US population. A study published in 2010 from the America On the Move study found that the average daily steps of adults in the United States is 5100 steps.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…25 Our study showed that activity of CV specialists is higher than the general US population. A study published in 2010 from the America On the Move study found that the average daily steps of adults in the United States is 5100 steps.…”
Section: Discussionmentioning
confidence: 50%
“…Work-related steps taken per day during work were not different among specialties or level of training and ranged between 4647 for medical consultants to 7907 for medical residents. 25 A study from Switzerland used pedometers to measure PA of 9 resident physicians for 1 week in a teaching hospital and found that the residents walked an average of 2323 ± 627 steps per work day. 28 However, it is important to mention that the primary objective of the study was not to measure PA of the residents.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have used pedometers to assess physical activity in the workplace, varying in sample size and length of observation (Aittasalo, Miilunpalo, & Suni, 2004;Chan, Ryan, & Tudor-Locke, 2004;Jatkinson, Goody, & Walker, 2005;Miller & Brown, 2004). Little research exists that has specifically examined the feasibility and acceptability of a 10,000…”
Section: > Backgroundmentioning
confidence: 99%
“…Outro estudo verificou se os médicos alcançavam as recomendações em termos de atividade física e concluiu que, embora as caminhadas no trabalho supram uma proporção substancial das necessidades diárias para os médicos, ainda é necessário o engajamento em horas adicionais de atividade física para que alcancem as recomendações 9 . Assim, pode-se argumentar que profissionais de saúde deveriam manter hábitos de vida saudáveis, pois dessa forma, seria mais fácil exercer a função de estimular a prática de atividade física no dia-a-dia profissional 10,11 .…”
Section: Introductionunclassified